O-11 Deactivation of implantable cardiac defibrillators at end-of-life: integrated working is essential. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Hodson, Fiona; DeCourcey, Julia; Karwatoski, Stefan; Albarjas, Mohammed; Ross, Joy; George, Rob
Abstract : Background: The benefits of integrated cardiac and palliative care support for patients with end-stage heart failure (ESHF) is well recognised (Jaarsma, Beattie, Ryder et al ., 2009; Hospice UK, 2017). NICE guideline support use of implantable cardiac defibrillators as part of optimal treatment. Guidelines recommend early discussion with 'careful, explicit, shared-decision making' to promote timely deactivation at end-of-life (NICE, 2014; British Heart Foundation, 2007). In practice this presents challenges for both professionals and patient/family, with varying and limited access to deactivation in the community setting. Methods: A case series is presented from a service evaluation of an integrated model of care for ESHF patients. 10/89 patients had implantable cardiac resynchronization therapy defibrillators (CRT-D) and 1/89 an implantable defibrillator (ICD). We present some of the challenges in management of these devices in our palliative cohort. Results: 8/10 devices were deactivated due to acute deterioration of patients; 1/10 patients reported shocks given. Timing of deactivation was arranged according to the patient's clinical condition and wishes, predominately within a month of death. Deactivation occurred in a variety of settings: hospital inpatient (3), hospital outpatient (3), home (1), hospice (1), including visits by electrophysiologists from tertiary centres and temporary use of magnets by clinicians. Discussions around deactivation of the CRT-D were complex due to previous clinical history and ingrained patient/family perceptions. Discussions were always multi-professional; one case was taken to the Hospice Clinical Ethics Committee. One patient had the defibrillator function deactivated and was subsequently resuscitated by the Ambulance Service when he went into fast atrial fibrillation. Family involvement and agreement with decision making was key, as was joint discussions by different professionals across care settings including those who had known the patient longest. Conclusion: These cases illustrate the need for further discussion and protocols regarding the time and place of deactivation of defibrillators at end of life, and also the challenges for professionals of having resuscitation discussions with these patients and importantly their families.